Provisions For Liabilities in Polish Business Entities In 2017-2021 - Małgorzata Białas; Isabella Emerling (Communications of International Proceedings, 2023)
The provisions created for future liabilities are the subject of this paper. The research was conducted on the basis of reports prepared by the Central Statistical Office in Poland in individual years from the period 2017-2021 and regarding the balance sheet results of business entities. The aim of this paper is to verify how the enterprises prepare for future liabilities by creating provisions. How the value of provisions has changed during Covid-19? In addition, attempts were made to answer the question in which industry the value of provisions is at the highest level.